Using Think-Pair-Share for writing descriptive texts - Rosnani Sahardin; Cut Salwa Hanum; Sofyan A. Gani (Universitas Syiah Kuala, 2017)
Using the right technique to teach writing is very important to help students overcome problems in writing. Think Pair Share (TPS) is a cooperative teaching-learning method that it is believed to help students improve their writing ability. Thus, the writers conducted an experimental study to tenth grade students at a senior high school in Banda Aceh to find out whether or not this technique could facilitate and improve the students’ writing of descriptive texts in English. The results showed that the TPS technique successfully improved the ability of students’ in writing, reflected by the post-test scores covering five aspects of writing. The progress before and after the technique was implemented can be seen in these average scores for the five aspects: content increased from 12 to 16, organization from 11 to 15, vocabulary from 9 to13, grammar from 8 to 10, and mechanics from 8 to 11 where the improvement for each aspect was 4, 4, 4, 2 and 3. Despite the results showed that the TPS technique was effective for improving the students’ mastery of organization, vocabulary and content, but less so for improving mechanics and grammar. This is probably because it is generally much easier to make improvements in organization, vocabulary and content but it requires a much longer effort with much more practice to significantly improve mechanics and grammar. Nevertheless, the writers suggest that English teachers and others can use the TPS technique to teach writing, hence some of the problems faced by students in writing can be helped and, more importantly, they can improve their ability to write English.